2005
DOI: 10.1002/joc.1130
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic climate change during the last 50 years

Abstract: The Reference Antarctic Data for Environmental Research (READER) project data set of monthly mean Antarctic nearsurface temperature, mean sea-level pressure (MSLP) and wind speed has been used to investigate trends in these quantities over the last 50 years for 19 stations with long records. Eleven of these had warming trends and seven had cooling trends in their annual data (one station had too little data to allow an annual trend to be computed), indicating the spatial complexity of change that has occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
754
2
48

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,017 publications
(861 citation statements)
references
References 27 publications
40
754
2
48
Order By: Relevance
“…. These observations were used to assess the change in near-surface conditions across the Antarctic over roughly the last 50 years (Turner et al, 2005). The seasonal and annual temperature trends are summarized for 15 stations in Figure 11.…”
Section: 17mentioning
confidence: 99%
See 1 more Smart Citation
“…. These observations were used to assess the change in near-surface conditions across the Antarctic over roughly the last 50 years (Turner et al, 2005). The seasonal and annual temperature trends are summarized for 15 stations in Figure 11.…”
Section: 17mentioning
confidence: 99%
“…Figure 11 shows that beyond the Antarctic Peninsula there were few statistically significant temperature changes in recent decades. In fact, of the 19 stations with long records examined by Turner et al (2005), 11 had warming trends in their annual data and 7 had cooling, with 1 station having too little data to allow the computation of an annual trend. An exception is the Amundsen-Scott station at the South Pole, which has experienced a cooling in all seasons, although only the annual trend of −0.17°C per decade is statistically significant at the 10% level.…”
Section: Thementioning
confidence: 99%
“…Increased intensity of the Amundsen Sea Low over recent decades has been associated with Antarctic-wide atmospheric changes that relate to the formation of the ozone hole Fogt and Zbacnik, 2014), and has dominated changes in wind stress across the region. Lower ozone concentrations over recent decades have been linked to summer strengthening (of $15-20%) of the large-scale clockwise winds, which have acted to further isolate Antarctica atmospherically (Turner et al, 2005a(Turner et al, , 2005b. This strengthening of the westerlies (Marshall et al, 2006) is demonstrated by changes in the Southern Annular Mode index, which is a measure of the principal mode of variability in the atmospheric circulation of the Southern Hemisphere (Fig.7).…”
Section: Atmospheric Conditions and Circulation In The Antarcticmentioning
confidence: 99%
“…et al, 2008b). This strengthening of the westerlies has contributed to cooling air temperatures over eastern Antarctica and the Antarctic plateau, but warming over the Antarctic Peninsula (Thompson and Solomon, 2002;Turner et al, 2005aTurner et al, , 2005bStammerjohn et al, 2008b). Regional warming in western Antarctica has also been linked to increased sea surface temperatures in the tropical Pacific that generate long, quasi-stationary atmospheric waves (Rossby waves), leading to southward advection of warm air associated with the Pacific South America Mode towards the west coast of Antarctica (Stammerjohn et al, 2008a;Ding et al, 2011).…”
Section: Atmospheric Conditions and Circulation In The Antarcticmentioning
confidence: 99%
“…If the surrounding oceans warm enough, then WAIS could rapidly disintegrate. Meanwhile, the Antarctic Peninsula, home to the northernmost fringes of WAIS, is undergoing perhaps the largest increase in temperature of any location on the planet (King et al, 2002;Turner et al, 2005), and there are already some warning signs that a WAIS collapse could be in progress. 3 Thus, abrupt WAIS collapse is a major cause for concern.…”
Section: Ice Melt and Sea Level Risementioning
confidence: 99%